The 6S‐model for person‐centred palliative care: A theoretical framework - Österlind, Jane (Nurs Philos, 2020)
Palliative care is provided at a certain timepoint, both in a person's life and in a societal context. What is considered to be a good death can therefore vary over time depending on prevailing social values and norms, and the person's own view and interpretation of life. This means that there are many interpretations of what a good death can actually mean for an individual. On a more general level, research in palliative care shows that individuals have basic common needs, for example physical, mental, social and spiritual well‐being. Therefore, in today's pluralistic Western society, it becomes important that palliative care is person centred to enable individuals to receive, as far as can be achieved, care that promotes as good a life as possible based on the person's own needs and preferences, and in accordance with evidence and current laws. For many years a research group, consisting nurse researchers together with nurses working in palliative care, has developed a model for person‐centred palliative care, the 6S‐model. The model's central concept is Self‐image, where the starting point is the patient as a person and their own experience of the situation. The other concepts: Self‐determination, Symptom relief, Social relationships, Synthesis and Strategies are all related to the patient's self‐image, and often to each other. The model's development, value base and starting assumptions are reported here, as are examples of how the model is applied in palliative care in Sweden. The model has been, and still is, constantly evolving in a collaboration between researchers and clinically active nurses, and in recent years also with patients and close relatives.